The Authenticity of Image using Hash MD5 and Steganography Least Significant Bit - Nurul Khairina; Muhammad Khoiruddin Harahap; Juanda Hakim Lubis (IJISTECH (International Journal of Information System and Technology), 2018)
A creation can be considered as belonging to someone if they have a valid proof. An original creation that have been changed for certain purposes will definitely eliminate proof of ownership of the creation. A hash function is one method used to test the authenticity of data, while steganography is one method used to maintain the security of confidential data from outside parties. In this study, the Hash MD5 method will be combined with the Least Significant Bit method to test the authenticity of an image. The purpose of testing the authenticity is to find out the truth of ownership of a creation, in this case, we are testing the image. The results of this test are the status of an image that will be declared valid or invalid. Measurement of validity depends on whether there is a similarity between the value of the Hash that has been implanted and the value of the Hash obtained during the test. If the tested image has the same Hash value, then the image will be declared valid, but instead ai image is declared invalid if the image has been modified or ownership status has been changed. From the result of testing the authenticity with several images, it can prove that the combination of the Hash MD5 method with LSB has a good level of security and suitable to authenticity testing.